INDUCTION SPAWNING FOR THE TROPICAL ABALONE (Haliotis asinina) IN THE LABORATORY - D.E. Djoko Setyono (Indonesian Aquaculture Journal, 2006)
The main purpose of this study was to test and understand the effectivity of previous successful treatment to induce spawning in temperate abalone, including the use of hydrogen peroxide, vigorous aeration, desiccation, thermal shock, and UV-irradiated seawater, to induce spawning in the tropical abalone (Haliotis asinina) from southern Lombok waters, NTB. Approximately 90% of mature animals conditioned in the laboratory could be spawned successfully. Wild freshly mature broodstock collected in the morning during spring low tide failed to spawn under any treatment tried, while in wild freshly mature broodstock collected in the afternoon during spring low tide, approximately 45% of the males and 37% of the females, spawned successfully under all treatments. Mature animals ready to spawn were usually found creeping up the tanks close to the water surface, and were very active but relaxed, and the foot was soft and flabby. In the laboratory, H. asinina from southern Lombok waters released gametes at night between 11:00 pm and 01:00 am. The conditioned broodstock had average batch fecundity ranged from 50,000 to 435,000 eggs and the freshly caught wild broodstock ranged from 50,000 to 105,000 eggs. Approximately 75% of spawned eggs were found to be ripe and the remaining 25% were unripe. In general, no artificial spawning induction is required to spawn tropical abalone (H. asinina) in laboratory (hatchery).